2014
DOI: 10.3892/ijo.2014.2387
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression signatures for identifying diffuse-type gastric cancer associated with epithelial-mesenchymal transition

Abstract: Abstract. Epithelial-mesenchymal transition (EMT) is associated with tumor malignancy. The hedgehog-EMT pathway is preferentially activated in diffuse-type gastric cancer (GC) compared with intestinal-type GC; however, histological typing is currently the only method for distinguishing these two major types of GC. We compared the gene expression profiles of 12 bone marrow-derived mesenchymal stem cell cultures and 5 diffuse-type GC tissue samples. Numerous upregulated or downregulated genes were identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 27 publications
2
56
0
Order By: Relevance
“…It has been reported that cadherin 1 ( CDH1 ) is up-regulated in diffuse-type GC cells compared to MSCs[9]. However, CDH2 was down-regulated in diffuse-type GC cells compared to MSCs; this provides a useful indicator - the ratio of CDH2 to CDH1 expression - to distinguish the mesenchymal and epithelial phenotypes of the cells[9]. It has been reported that catenin β 1 ( CTNNB1 ) is mutated in hepatocellular carcinoma[10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that cadherin 1 ( CDH1 ) is up-regulated in diffuse-type GC cells compared to MSCs[9]. However, CDH2 was down-regulated in diffuse-type GC cells compared to MSCs; this provides a useful indicator - the ratio of CDH2 to CDH1 expression - to distinguish the mesenchymal and epithelial phenotypes of the cells[9]. It has been reported that catenin β 1 ( CTNNB1 ) is mutated in hepatocellular carcinoma[10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The metastatic process included tumor cell detachment, local invasion, motility, angiogenesis, vessel invasion, survival in the circulation, adhesion to endothelial cells, extravasation, and regrowth in different organs. [30,31] Interestingly, 25.5% of these genes were primarily involved in cell adhesion, cell migration, extracellular matrix disassembly, blood vessel development, and wound healing associated with gastric adenocarcinoma metastases, such as collagen families, [20,23,32,33] fibronectin 1, [20,23,34] and matrix metalloproteinases (MMPs) families. [20,23,3539] Some cell proliferation-related genes, such as MYC, [20,23,40] cyclin E1, [20,23,41] CDC28 protein kinase regulatory subunit 1, [20,42,43] CDC28 protein kinase regulatory subunit 2, [23,43] cyclin-dependent kinase 4, [20,23,44] and proliferating cell nuclear antigen, [20,44,45] EGFR, [20,44,46] FGFR4, [20,23] insulin like growth factor 2, [20] cell division cycle 25B, [47] human epidermal growth factor receptor 2, [44,45] and protein kinase, DNA-activated, catalytic polypeptide, [48] have been previously reported as showing extremely high levels of expression in gastric adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The epithelial-mesenchymal transition (EMT) is a process by which epithelial cells lose their cell polarity and normal cell-cell contacts, and become migratory, invasive, and mesenchymal stem cell-like [6]. Normal mesenchymal stem cells are multipotent stromal cells that can differentiate into a variety of cell types so that EMT has a role in tissue regeneration, such as in response to wounding.…”
Section: Introductionmentioning
confidence: 99%